Sometimes I cry - Townes, Jess (Farrar Straus Giroux, 2023)
"There are all sorts of feelings that can make us cry--from disappointment to joy, from grief to love. Sometimes I Cry offers a gentle and necessary affirmation of the emotional complexity of growing up. Powerful, poignant, and universally relevant, it is a triumph for readers of any age"--